Grado de satisfacción de los usuarios de la agencia BanEcuador de Ventanas - Valero Segura, Jeniffer Briggitte (2018)
The case study is framed in the line of research administrative management model, the methodology applied in the investigation is descriptive, which will allow to discover the characteristics that influence the problems addressed by the financial institution. It was used as a collection technique, a survey to external users of the BanEcuador and an interview with the cantonal manager of the financial institution to gather the necessary information to be able to carry out this case study.